Deep neck infection after third molar extraction: A case report - Alberto Ferreira da Silva Junior; Gustavo Silvestre de Magalhaes Rocha; Camila Fialho da Silva Neves de Araujo; Ademir Franco; Rhonan Ferreira Silva (Tabriz University of Medical Sciences, 2017)
Deep neck infections are associated with high morbidity rates in dentistry. Early diagnosis and intervention play an essential part in decreasing morbidity rates. The present study aims to report a case of odontogenic deep neck infection after third molar extraction. A 51-year-old male patient underwent extraction of the mandibular right third molar. Seven days later, the patient developed symptoms and signs of progressive infection. Laboratorial and radiologic examinations in association with clinical investigations confirmed deep neck infection. Extraoral drainage was performed under orotracheal intubation. Postoperative laboratory tests and clinical examinations revealed signs of complete remission within a follow-up period of 10 days. Considering the invasive nature of pathogens related to deep neck infections, it is possible to infer that a combination of accurate diagnosis and early intervention plays an essential role in the field of maxillofacial surgery and pathology.